Exploring the factors affecting user satisfaction of dialog axiata plc company products: A systematic review - Kajanthy, K.; Vivek, R. (University of Jaffna, 2020)
Customer satisfaction is the central theme of this study. Dialog Axiata PLC has been selected for this research. This company is a leading communication service provider under the telecommunication industry in Sri Lanka. However, according to the market observation of the management of Dialog Axiata PLC, customer satisfaction is not seemed as favourable because the number of customers is declining over the last few years. By taking this information as a basis, researchers have explored the factors that affect customer satisfaction in the Sri Lankan Telecommunication industry. The objectives of this study are to explore the factors that influence customer satisfaction on the services provided by Dialog Axiata PLC and suggest strategies to improve Dialog Axiata PLC's customer satisfaction level. Researchers of this study have established qualitative research and deductive approach since all data presented is based on past research articles and models. As the sample of the study, the researchers selected ten relevant research articles and factors that affect customer satisfaction. To analyse the factors affecting customer satisfaction, the thematic analysis and narrative writing from the existing literature have been used. Based on the identified factors that determine customer satisfaction, the relevant factors for the context of the Sri Lankan Telecommunication Industry, have been selected and incorporated into the researchers’ developed conceptual framework. The conceptual framework was developed based on the factors, which are most appropriate to the Sri Lankan Telecommunication Industry such as app performance (low interruptions), complaints management, empathy, pricing, reliability and social media memes. Those identified factors have been considered as predictors (Independent variables) of customer satisfaction (Dependent variable) of telecommunication customers. Finally, future researchers are motivated to gather more definite findings by collecting primary data and measuring data to analyse these factors. And also, they can explore other key factors that may have an impact on customer satisfaction. This conducted research work fulfilled the knowledge gap on the area of factors affecting the satisfaction of customers who was benefitting from the products and services of telecommunication companies and enhanced the knowledge of researchers of the current study and future studies on this theme.
Keywords: App performance; Customer satisfaction; Social media memes and telecommunication industry